PDMP induces rapid changes in vacuole morphology in arabidopsis root cells - Krüger, Falco; Krebs, Melanie; Viotti, Corrado; Langhans, Markus; Schumacher, Karin; Robinson, David G. (The journal of experimental botany, 2013)
PDMP (d-l-threo-1-phenyl-2-decanoyl amino-3-morpholino-1-propanol) is a well-known inhibitor of glucosylceramide synthase (GCS), a key enzyme in sphingolipid biosynthesis. Through the resultant increase in ceramides which interact with mTOR and Beclin1 (Atg6), this drug is also known to induce macroautophagy in mammalian cells. This study investigated the response of Arabidopsis root cells to PDMP, and what are probably numerous tightly packed small vacuoles in the control cells appear to fuse to form a single globular-shaped vacuole. However, during this fusion process, cytoplasm channels between the individual vacuoles become trapped in deep invaginations of the tonoplast. In both optical sections in the confocal laser scanning microscope and in ultrathin sections in the electron microscope, these invaginations have the appearance of cytoplasmic inclusions in the vacuole lumen. These changes in vacuole morphology are rapid (occurring within minutes after application of PDMP) and are independent of ongoing protein synthesis. The tonoplast invaginations remain visible for hours, but after 24h almost all disappear. Experiments designed to examine whether ceramide levels might be the cause of the PDMP effect have not proved conclusive. On the other hand, this study has been able to rule out the release of Ca2+ ions from intracellular stores as a contributing factor.
Published online: 10 December 2012
Gesehen am 25.07.2017